The relationship of the formulas for the number of connected vertices labeled graphs with order five and order six without loops - Amanto, Amanto; Notiragayu, Notiragayu; Zakaria, La; Wamiliana, Wamiliana (Universitas Islam Negeri Raden Intan Lampung, 2021)
Given a graph with n points and m lines. If each vertex is labeled, then it can be constructed many graphs, connected, or disconnected graphs. A graph G is called a connected graph if there is at least one path that connects a pair of vertices in G. In addition, the graph formed may be simple or not simple. A simple graph is a graph that does not contain loops or parallel lines. A loop is a line that connects a point to itself, and a parallel line is two or more lines that connect the same pair of points. This paper will discuss the relationship between the formula patterns for calculating the number of connected graphs labeled with vertices of order five and six without loops.